Karakteristik Dangke Susu Kerbau dengan Penambahan Crude Papain Kering - Sulmiyati Sulmiyati; Nur Saidah Said (agriTECH, 2018)
Dangke is traditional food from Enrekang, South Sulawesi, which is made from coagulated  buffalo milk or cow milk protein by using crude papain.  There is limited information about characteristics of dangke from buffalo milk than those from cow milk. The characteristics of dangke is affected by the addition of crude papain. This study was aimed to explore the effect of crude papain addition to curd dangke production,  percentage of whey and taste of dangke from buffalo milk. This study was conducted by using complete randomized design with 4 treatments and 5 repetitions. Treatments consist of the addition of crude papain in different concentration:  0.5%;  1%;  1.5% and 2.0%.  This study howed that curd dangke production range was 41.38- 52.20; pH range was 6.92- 6.96; lactic acid percentage range is 0.15-0.70;  curd dangke's colour range was 1.35 (white)- 1.50 (white);  smell range was 2.50 (mild dangke' smell)- 3.55 (mild dangke' smell);  taste range was 2.10 (bitter)- 4.60 (not bitter) and preference level range was 2.00 (dislike)- 3.90 (like). This study revealed that the best quality of dangke from buffalo milk was derived from treatments with addition of 1% crude papain. Physicochemistry characteristics from our dangke: curd dangke production was 43.94%;  whey percentage was 51.14;  pH was 6.96;  lactic acid percentage was 0.15.  Organoleptic characteristics: curd dangke's colour was 1.45 (white), smell was 2.55 (mild dangke' smell), taste was 4.10 (slightly bitter)  and preference level was 3.55 (like).